2016
DOI: 10.1016/j.jelekin.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repetitive ankle perturbations on muscle reaction time and muscle activity

Abstract: The use of a tilt platform to simulate a lateral ankle sprain and record muscle reaction time is a well-established procedure. However, a potential caveat is that repetitive ankle perturbation may cause a natural attenuation of the reflex latency and amplitude. This is an important area to investigate as many researchers examine the effect of an intervention on muscle reaction time. Muscle reaction time, peak and average amplitude of the peroneus longus and tibialis anterior in response to a simulated lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…As opposed to these results, Di Giminiani and collagenous investigated the EMGRMS activities in the GL at different frequencies and positions. Their results indicate that lower frequencies of vibration (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) resulted in maximal activation of GL (averaged values of four body positions) than higher frequencies [6]. They suggested that ankle muscles were highly influenced by body position therefore, the different body positions may be affected the findings.…”
Section: The Study Was Supported By Gazi University Projects Of Scienmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to these results, Di Giminiani and collagenous investigated the EMGRMS activities in the GL at different frequencies and positions. Their results indicate that lower frequencies of vibration (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) resulted in maximal activation of GL (averaged values of four body positions) than higher frequencies [6]. They suggested that ankle muscles were highly influenced by body position therefore, the different body positions may be affected the findings.…”
Section: The Study Was Supported By Gazi University Projects Of Scienmentioning
confidence: 99%
“…Tibialis anterior -1/3 on the line between the tip of the fibula and the tip of the medial malleolus; peroneus longus -25% on the line between the tip of the head of the fibula to the tip of the lateral malleolus; gastrocnemius medialis -on the most prominent bulge of the muscle; and gastrocnemius lateralis -1/3 of the line between the head of the fibula and the heel) [12,29,34]. All electrodes were fixed by double-sided tape to guarantee that they remain stable throughout the session and the cables were carefully fixed by tape to the skin.…”
Section: Whole-body Vibration Protocolmentioning
confidence: 99%
“…Other health issues are related to physical [11,12] and psychological effects [21]. Some research has focused on ergonomics [22,23] and suggests that poor ergonomic design can have a negative result on a worker's musculoskeletal system, resulting in muscle fatigue [24], and may even progress into musculoskeletal disease [25]. All these health issues take time to develop.…”
Section: Health and Safety In The Manufacturing Industrymentioning
confidence: 99%
“…The time latency required for peroneal muscles to react against a sudden inversion perturbation is termed as peroneal reaction time (Thain et al, 2016). Peroneal reaction time in healthy ankle ranged from 55 to 85 ms (Dufek & Bates, 1991;Eechaute et al, 2009;Fernandes et al, 2000;Hoch & McKeon, 2014;Konradsen & Bohsen Ravn, 1991;Konradsen et al, 1998;Hopkins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%